Implementation of Research Results in Preparing a Housing Planning Textbook - Sri Suryani Yuprapti Winarsih; Muchlisiniyati Safeyah; Lily Syahrial (Future Science)
Learning is an activity undertaken by students to achieve educational goals. This learning process takes place in the interaction between the components of students (students) and educators (lecturers) with the content of educational goals. While learning outcomes can be classified into three, 1) effectiveness, which is measured by the level of student achievement, 2). Efficient, measured by the ratio between effectiveness and the amount of study time and/or the number of learning costs, 3). Attractiveness, which is measured by observing the tendency of students to keep learning. Housing planning is one of the courses taught in UPNVJT Architecture education that studies the elements, guidelines, and provisions involved in planning a residential environment. This Textbook is the result of previous research entitled